Knowledge Structure and the Estimation of Conditional Probabilities in Audit Planning. - Nelson, Mark W.; Libby, Robert; Bonner, Sarah E. (The Accounting Review, 1995)
Abstract Presents the results of an experiment which focuses on the mismatch between auditors' tendency to structure their knowledge of financial statement errors with audit objective. Audit tasks' requirement of auditors' assessment of objectives; Effects of knowledge structures' mismatch with task structures.